Lessons Learned From Implementing an Incident Command System During a Local Multiagency Response to a Legionnaires' Disease Cluster in Sydney, NSW. (5th September 2017) - Quinn, Emma; Johnstone, Travers; Najjar, Zeina; Cains, Toni; Tan, Geoff; Huhtinen, Essi; Nilsson, Sven; Burgess, Stuart; Dunn, Matthew; Gupta, Leena
Abstract: The incident command system (ICS) provides a common structure to control and coordinate an emergency response, regardless of scale or predicted impact. The lessons learned from the application of an ICS for large infectious disease outbreaks are documented. However, there is scant evidence on the application of an ICS to manage a local multiagency response to a disease cluster with environmental health risks. The Sydney Local Health District Public Health Unit (PHU) in New South Wales, Australia, was notified of 5 cases of Legionnaires' disease during 2 weeks in May 2016. This unusual incident triggered a multiagency investigation involving an ICS with staff from the PHU, 3 local councils, and the state health department to help prevent any further public health risk. The early and judicious use of ICS enabled a timely and effective response by supporting clear communication lines between the incident controller and field staff. The field team was key in preventing any ongoing public health risk through inspection, sampling, testing, and management of water systems identified to be at-risk for transmission of legionella. Good working relationships between partner agencies and trust in the technical proficiency of environmental health staff aided in the effective management of the response. ( Disaster Med Public Health Preparedness . 2018;12:539–542)